Tailoring Resorption Rates and Osteogenic Response in Xeno-Hybrid Bone Grafts: The Effect of Added Gelatins. (June 2022) - Zhu, Hao; Haugen, Håvard Jostein; Perale, Giuseppe; Elin Reseland, Janne; Parreiras Nogueira, Liebert; Gonzalez Cantalapiedra, Antonio; Maria Guzon Muñoz, Fernando; Permuy Mendaña, Maria; Betge, Felice; Petter Lyngstadaas, Ståle; Xiao, Jun
Abstract: Bone defects resulting from trauma, surgery, congenital malformations, and other factors are among the most common health problems nowadays. Although current strategies such as autografts and allografts are recognized as the most successful treatments for stimulating bone regeneration, limitations such as graft source and complications still exist. SmartBone® is a xeno-hybrid bone graft (made from bovine bone matrix, poly( L -lactic- co -ε-caprolactone), and gelatin) with a positive clinical record for bone regeneration. In this study, the formulation for designing xeno-hybrid bone grafts using gelatins from different sources (bovine- and porcine-derived gelatin, with bone grafts named SBN and SPK, respectively) was investigated, and the biological responses were evaluated in vitro and in vivo . The results demonstrate that gelatins from both bovine and porcine sources can be loaded onto SmartBone® successfully and safely, withstanding the aggressive manufacturing processes. Different bone cell responses were observed in vitro . SBN was found to enhance osteocalcin secretion while SPK was found to upregulate osteopontin from human osteoblasts. In vivo, both bone grafts promoted osteogenesis, but SPK degraded earlier than SBN. Our findings suggest that SBN and SPK provide different yet comparable solutions for optimizing the bone resorption and regeneration balance. These xeno-hybrid bone grafts possess ideal potential for bone defect repairing.